Analisis Pengaruh Lingkungan Belajar Berbasis Model Inquiry Terhadap Sikap Lifelong Learning dalam Matematika - Iksal, Iksal; Al-Amin, Al-Amin (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This study aims to analyze the effect of inquiry model-based learning environment on lifelong learning attitude in mathematics. The method used is a literature review by reviewing various relevant studies and scientific articles. The results of the analysis show that the inquiry model, which encourages students to ask questions, research, and discover concepts independently, has a positive impact on the development of lifelong learning attitudes. The inquiry-based learning environment creates an atmosphere that supports exploration and deep understanding of mathematical materials. The critical attitude, curiosity, and problem-solving skills gained from the model can encourage students to continue learning for life. Thus, the implementation of inquiry-based learning environment can be an effective strategy to build lifelong learning attitude in mathematics education. This study provides important insights for educators and policy makers in developing innovative and sustainable curriculum and learning methodologies.